Asymptomatic Bacteriuria in Diabetic Adults - Adhikaree, Ajay; Kohli, Suresh Chandra; Pokhrel, Daya Ram; Bhatta, Dharma (Journal of Lumbini Medical College, 2016)
Introduction: Urinary Tract Infection (UTI) is a well- known complication of Diabetes Mellitus (DM). Its spectrum ranges from Asymptomatic Bacteriuria (ABU) to acute pyelonephritis. Many studies have delineated an increased prevalence of ABU in DM whereas to the same degree other studies have come to naught showing insignificant association. Hence, this study was drafted to evaluate the presence of ABU among diabetics and assess various risk factors. Methods: Total of 116 diabetic adults without symptoms of UTI attending medical out-patient department, Manipal Teaching Hospital were enrolled by detailed clinical history, examination and laboratorial examination as per standard set of questionnaire from February 2013 to May 2014. Data were analyzed by SPSS (17.0). Results: The rate of ABU in diabetic adults was 10.3% and was significantly associated with duration of DM, fasting blood glucose level and poor glycogenic control. Escherichia coli were the most frequently isolated pathogen which was sensitive to Nitrofurantoin and Impanel. Conclusion: Being asymptomatic, diabetics fail to recognize ABU, however, ABU is preponderant in DM and is linked mainly with duration of DM and poor glycogenic control. Hence screening for ABU is imperative in diabetic adults if above mentioned risk factors are present. DOI: https://doi.org/10.22502/jlmc.v3i2.66 J. Lumbini. Med. Coll. Vol 3, No 2, July-Dec 2015